Correlation of Trace Element Imbalance with the Pathogenesis of Oral Submucous Fibrosis and Its Implications in Prosthodontic Rehabilitation - Omer Masood Alam Shad, Qurat-Ul-Ain, Zainab Niazi, Azam Shahzad, Farhan Riaz, Munazza Javed (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Oral Submucous Fibrosis (OSF) is a chronic, progressive condition characterized by fibrosis and restriction of oral mucosal tissues. It is primarily associated with areca nut chewing, which is prevalent in many parts of Asia. Imbalances in trace elements, such as zinc, copper, iron, and selenium, may influence the pathogenesis and severity of OSF. Objectives: To investigate the correlation between trace element imbalances and the severity of OSF in a Pakistani population, focusing on zinc, copper, iron, and selenium levels. Study Design & Setting: This study employed a cross-sectional design, conducted in Dentistry Department Abbottabad International Dental College. Methodology: It included 120 patients diagnosed with OSF, with different stages of severity (Grade 1, 2, and 3). Blood samples were collected from all participants, and trace element levels (zinc, copper, iron, and selenium) were analyzed using Atomic Absorption Spectroscopy (AAS). The severity of OSF was clinically categorized into Grade 1, 2, and 3 based on mouth opening and mucosal changes. Statistical analysis, including Pearson’s correlation coefficient, was used to assess the relationship between trace element imbalances and OSF severity. Results: Significant correlations were found between the levels of trace elements and OSF severity. Zinc levels decreased with increasing OSF grade, while copper and iron levels increased. Selenium levels showed minimal correlation. Practical Implication: The findings suggest that trace element imbalances may play a role in OSF pathogenesis and could be targeted in future therapeutic strategies. Conclusion: This study highlights the potential impact of trace element imbalances on OSF severity, emphasizing the need for further research on dietary interventions. Keywords: Copper, Iron, OSF, Selenium, Trace Elements, Zinc